2017
DOI: 10.3390/en10020156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Distributed Generation Grid Code Requirements on Islanding Detection in LV Networks

Abstract: Abstract:The recent growing diffusion of dispersed generation in low voltage (LV) distribution networks is entailing new rules to make local generators participate in network stability. Consequently, national and international grid codes, which define the connection rules for stability and safety of electrical power systems, have been updated requiring distributed generators and electrical storage systems to supply stabilizing contributions. In this scenario, specific attention to the uncontrolled islanding is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…Although the anti-islanding mechanisms defined by current regulatory frameworks proved to be effective in most cases, recent studies demonstrated that, under the different stabilizing functions required by national and international grid codes, the measurement techniques implemented in current IPSs could be inadequate [9]. Anti-islanding protection functions could in fact fail, particularly during transients, due to the masking effect of stabilizing functions on IPSs [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although the anti-islanding mechanisms defined by current regulatory frameworks proved to be effective in most cases, recent studies demonstrated that, under the different stabilizing functions required by national and international grid codes, the measurement techniques implemented in current IPSs could be inadequate [9]. Anti-islanding protection functions could in fact fail, particularly during transients, due to the masking effect of stabilizing functions on IPSs [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a thorough study is needed in solving this issue. Hence, anti-islanding with fast response time is essential for a DG connected grid system [10,16]. To overcome the challenges from islanding DGs, researchers proposed a numerous model that deals with the consequences of intentional islanding, and clears it as fast as possible [11,12,[17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The highest penetration of PV systems is at the distribution level, in fact 95% of the PV systems are connected to the medium voltage (MV) and low voltage (LV) level [4], in which the topology of the network is essentially radial. At micro-generating level, the European Standard CENELEC EN 50438 contains the rules for the connection of electrical power plants with a rated current below 16 A, to the LV distribution network [5,6]. For what concerns the voltage quality, the European Standard EN 50160 limits the voltage deviation to an interval of ±10% of the rated value [7].…”
Section: Introductionmentioning
confidence: 99%